Einstein in Kafkaland : how Albert fell down the rabbit hole and came up with the universe - Krimstein, Ken (Bloomsbury Publishing, 2024)
During the year that Prague was home to both Albert Einstein and Franz Kafka from 1911-1912, the trajectory of the two men's lives wove together in uncanny ways--as did their shared desire to tackle the world's biggest questions in Europe's strangest city. In stunning words and pictures, Einstein in Kafkaland reveals the untold story of how their worlds wove together in a cosmic battle for new kinds of truth. For Einstein, his lost year in Prague became a critical bridge set him on the path to what many consider the greatest scientific discovery of all time, his General Theory of Relativity. And for Kafka, this charmed year was a bridge to writing his first masterpiece, The Judgment. Based on diaries, lectures, letters, and papers from this period amid a planet electrifying itself into modernity, Einstein in Kafkaland brings to life the emergence of a new world where art and science come together in ways we still grapple with today.